2022
DOI: 10.3389/fnins.2022.945221
|View full text |Cite
|
Sign up to set email alerts
|

Focal non-invasive deep-brain stimulation with temporal interference for the suppression of epileptic biomarkers

Abstract: IntroductionNeurostimulation applied from deep brain stimulation (DBS) electrodes is an effective therapeutic intervention in patients suffering from intractable drug-resistant epilepsy when resective surgery is contraindicated or failed. Inhibitory DBS to suppress seizures and associated epileptogenic biomarkers could be performed with high-frequency stimulation (HFS), typically between 100 and 165 Hz, to various deep-seated targets, such as the Mesio-temporal lobe (MTL), which leads to changes in brain rhyth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
34
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 49 publications
(36 citation statements)
references
References 51 publications
1
34
1
Order By: Relevance
“…As illustrated in Figure 1A, standard TI creates deep subcortical stimulation by a combination of two kHz frequencies applied through two pairs of electrodes, where the field from the first pair (red) and the field from the second pair (light red) overlap to create a region with strong envelope modulation (yellow). The frequency of the envelope is equal to the difference between the two kHz frequencies and is set to a value equal to a frequency from traditional deep brain stimulation to be non-invasively replicated – for example in the hippocampus 50Hz for excitation or 130Hz for inhibition in accordance with our previous publications on TI stimulation in epilepsy 13 . Neural activity can only be influenced in the region of overlap, where a significant low-frequency envelope results, as the minimally modulated kHz exposure outside that region does not efficiently drive neuronal activity.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…As illustrated in Figure 1A, standard TI creates deep subcortical stimulation by a combination of two kHz frequencies applied through two pairs of electrodes, where the field from the first pair (red) and the field from the second pair (light red) overlap to create a region with strong envelope modulation (yellow). The frequency of the envelope is equal to the difference between the two kHz frequencies and is set to a value equal to a frequency from traditional deep brain stimulation to be non-invasively replicated – for example in the hippocampus 50Hz for excitation or 130Hz for inhibition in accordance with our previous publications on TI stimulation in epilepsy 13 . Neural activity can only be influenced in the region of overlap, where a significant low-frequency envelope results, as the minimally modulated kHz exposure outside that region does not efficiently drive neuronal activity.…”
Section: Resultsmentioning
confidence: 99%
“…The method simultaneously applies two high frequency electric fields -too high to activate neurons individually -with slightly differing frequencies, thus allowing the fields to constructively and destructively interfere in time, resulting in an amplitude-modulated field. Neurons have been shown by us and by others to respond to the amplitude modulated field [8][9][10] . As a result, it is possible to restrict neurostimulation to the region where the two fields overlap.…”
Section: Introductionmentioning
confidence: 93%
See 1 more Smart Citation
“…For instance, the group of Williamson reported that TI stimulation with envelop frequency around 130 Hz effectively suppressed the epileptic seizure in the hippocampus of rat models, while transcranial current stimulation in the same frequency failed to reach such deep brain tissue (Figure 5B,C). [48] Furthermore, the group of Williamson was devoted to combining TI Figure 6. Genetics-based neuromodulation.…”
Section: Non-genetic Neuromodulationmentioning
confidence: 99%
“…applications(Missey et al, 2021;Missey et al, 2022;Acerbo et al, 2022). However, peripheral nerve stimulation using TI is not common(Botzanowski et al, 2021), especially for targeting facial nerves.…”
mentioning
confidence: 99%